Effects of mutational combinations on philadelphia-negative myeloproliferative neoplasms - Yönal-Hindilerden, İpek; Dağlar-Aday, Aynur; Hindilerden, Fehmi; Nalcacı, Meliha; Akif, Selim Yavuz; Sargın, Deniz (Shiraz Univ Medical Sciences, 2017)
Philadelphia-negative myeloproliferative neoplasms (MPNs) were first described 65 years ago. Yet, the molecular features of the disease have become of interest since 2005 following the identification of the JAK2V617F mutation.1 Between 90% and 98% of patients with polycythemia vera and about 50% of patients with essential thrombocythemia (ET) and primary myelofibrosis (PMF) harbor the JAK2V617F mutation.2 In recent years, additional genetic factors such as the mutations of IDH1/2, TET2, EZH2, ASXL1, and CALR have been identified in Ph-negative MPNs.3 However, the significance of mutational combinations on Ph-negative MPNs remains unknown.
WOS: 000399199200015
PubMed ID: 28360451
Keywords: Mutational Combinations; Philadelphia-Negative Myeloproliferative Neoplasms